2022
DOI: 10.1021/acs.inorgchem.2c00180
|View full text |Cite
|
Sign up to set email alerts
|

The One-Electron Reduced Active-Site FeFe-Cofactor of Fe-Nitrogenase Contains a Hydride Bound to a Formally Oxidized Metal-Ion Core

Abstract: The nitrogenase active-site cofactor must accumulate 4e − / 4H + (E 4 (4H) state) before N 2 can bind and be reduced. Earlier studies demonstrated that this E 4 (4H) state stores the reducing-equivalents as two hydrides, with the cofactor metal-ion core formally at its resting-state redox level. This led to the understanding that N 2 binding is mechanistically coupled to reductive-elimination of the two hydrides that produce H 2 . The state having acquired 2e − /2H + (E 2 (2H)) correspondingly contains one hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…A way to sort out these problems is to study simpler states with a lower number of possibilities. Most computational , and experimental , studies agree that the E 1 state involves the protonation of the S2B μ 2 -bridging sulfide ligand of the FeMo cluster (but a recent experimental study of Fe-nitrogenase instead suggested a hydride ion).…”
Section: Introductionmentioning
confidence: 99%
“…A way to sort out these problems is to study simpler states with a lower number of possibilities. Most computational , and experimental , studies agree that the E 1 state involves the protonation of the S2B μ 2 -bridging sulfide ligand of the FeMo cluster (but a recent experimental study of Fe-nitrogenase instead suggested a hydride ion).…”
Section: Introductionmentioning
confidence: 99%
“…The results are in line with a recent X-ray study, 9 but in strong disagreement with a recent EPR study. 10 The accuracy of the present calculations has been benchmarked on a set of redox enzymes indicating an accuracy of about 3 kcal mol À1 , also for the redox transitions, for all of them. 12 Also, the results for the N 2 activation in E 4 is in perfect agreement with observations by EPR.…”
Section: Discussionmentioning
confidence: 89%
“…Recent experiments have shown that the ground state for the cofactor of V-nitrogenase has the redox state (3Fe(II), 4Fe(III), V(III)), which is an S = 0 (or integer spin non-Kramers) state. 18 To repeat, the EPR study led to a suggested structure with a bridging hydride for E 1 , 10 while the X-ray study led to a suggested protonated belt sulfide. 9 Therefore, the suggested oxidation states were quite different with (2Fe(II), 5Fe(III), Mo(III)) for the EPR study and (4Fe(II), 3Fe(III), Mo(III)) for the X-ray study.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The experiments concerned studies of a state obtained after only one reduction generally termed the E 1 state. In one study using X‐ray spectroscopy, it was concluded that there is a reduction of one of the irons and no hydride is present [34], while in an EPR study it was concluded that there should be a hydride present, implying that one of the irons is instead oxidized [35]. At present, model calculations suggest a hydride in the E 1 state, but no hydride in the A 1 state.…”
Section: Discussionmentioning
confidence: 99%